Digital science fiction as a narrative mediator for STEM motivation in elementary education: a mixed-methods study - Londoño-Proaño, Cristián; Pérez-Gavilanes, Verónica (Frontiers in Education, 2026)
This study aims to analyze the impact of the digital science fiction story “The Infinite Name of the Stars” on motivation toward STEM (science, technology and mathematics) subjects in elementary school students. A mixed approach was applied, combining a quasi-experimental pretest-posttest quantitative design with ethnographic observation in the classroom. The sample has 110 students. The quantitative results showed a stable and positive attitude toward science, with slight increases in curiosity, taste for mathematics and preference for science fiction narrative materials. The qualitative findings revealed enthusiasm, imagination and symbolic appropriation, expressed in dramatizations, infographics, and drawings. The triangulation of the findings suggests that science fiction narrative favors meaningful learning by connecting emotion, imagination, and scientific knowledge. In conclusion, the digital story functioned as a narrative mediator to promote motivation and scientific literacy from the literary experience.